How the Realism of Robot Is Needed for Individuals With Autism Spectrum Disorders in an Interview Setting - Kumazaki, Hirokazu; Muramatsu, Taro; Yoshikawa, Yuichiro; Matsumoto, Yoshio; Miyao, Masutomo; Ishiguro, Hiroshi; Mimura, Masaru; Minabe, Yoshio; Kikuchi, Mitsuru (Frontiers in Psychiatry, 2019)
The preliminary efficacy of interview training using an android robot whose appearance and movements resemble those of an actual human for treating social and communication difficulties in individuals with autism spectrum disorders (ASD) has been demonstrated. Patient preferences regarding the appearance of robots are crucial for incentivizing them to undergo robot-assisted therapy. However, very little is known about how the realistic nature of an android robot is related to incentivizing individuals with ASD in an interview setting. In this study, individuals with ASD underwent an interview with a human interviewer and an android robot. Twenty-three individuals with ASD (age, 17-25 years) participated in this study. After the interview, the participants were evaluated in terms of their motivation to practice an interview with an android robot and their impression of the nature of the android robot in terms of humanness. As expected, subjects exhibited higher motivation to undergo interview training with an android robot than with a human interviewer. Higher motivation to undergo an interview with the android robot was negatively correlated with the participants’ impressions of the extent to which the android robot exhibited humanness. This study brings us one step closer to understanding how such an android robot should be designed and implemented to provide sufficiently realistic interview training that can be of therapeutic value.